New drugs in early-stage clinical trials for allergic rhinitis. (4th March 2019) - Heffler, Enrico; Brussino, Luisa; Del Giacco, Stefano; Paoletti, Giovanni; Minciullo, Paola Lucia; Varricchi, Gilda; Scadding, Guy; Malvezzi, Luca; De Virgilio, Armando; Spriano, Giuseppe; Puggioni, Francesca; Fornero, Monica; et al.
ABSTRACT: Introduction : Allergic rhinitis (AR) is the most common allergic disease, and it has a relevant impact on the quality of life of the patient. Treatment of AR includes a combination of strategies of proven efficacy and effectiveness; however, a relevant proportion of patients remain uncontrolled. Areas covered : This review article summarizes emerging therapeutic approaches to AR; these approaches include nasal sprays, oral drugs, alternative allergen immunotherapy administration routes, and biologic agents. Expert opinion : The agents discussed require further clinical trials to prove their efficacy in the treatment of AR. Some of these agents, in particular, allergen immunotherapies and biologics, have the potential to form crucial precision medicine approaches to AR. Those that prove their efficacy in clinical trials must also be evaluated from a pharmacoeconomic perspective, possibly in real-life studies; this will define which therapeutic strategies achieve the most convenient and cost-effective ratio, thus yielding a novel opportunity for the most severe and previously treatment-resistant allergic patients.